Ironing out differences in attenuation and blooming artifact in acute stroke thrombi - Aglae Velasco Gonzalez; Dennis Görlich; Boris Buerke; Cristina Sauerland; Norbert Meier; Manfred Fobker; Ray McCarthy; Astrid Jeibmann; Walter Heindel; Andreas Faldum; Harald Kugel (Scientific Reports)
Abstract This study aims to improve our understanding of acute ischemic stroke clot imaging by integrating CT attenuation information with MRI susceptibility signal of thrombi. For this proof-of-principle experimental study, fifty-seven clot analogs were produced using ovine venous blood with a broad histological spectrum. Each clot analog was analyzed to determine its RBC content and chemical composition, including water, Fe III, sodium, pH, and pO2. Non-contrast CT and a susceptibility-weighted MRI sequence were used for imaging. The study found that RBC content correlated more accurately than iron content with clot attenuation on CT. There was a strong correlation between Fe III content and RBC percentage in clots. Specifically, changes in RBC content accounted for 64% of the variance in Fe III content (R2 = 0.640; p < .0001). Thrombi with blooming artifacts (BA) displayed higher attenuation on non-contrast CT than those without (73.4 vs. 40 HU, p < .0001) and had the highest RBC and iron contents. The cut-off value of 1242 µg/g of iron predicted blooming artifacts with high sensitivity and specificity. The pH level strongly affected the appearance of blooming artifacts, particularly for negative clots with high RBC content. These findings provide significant insights into the imaging behavior of acute ischemic stroke clots across both imaging modalities and could potentially improve the diagnosis and treatment of acute stroke patients. Furthermore, these results open the possibility for future research aimed at developing pH-modulated therapeutic strategies based on the acid-base state of thrombi.